STUDI IDENTIFIKASI PENANGGULANGAN BANJIR DAN DESAIN DREINASE JLN.INPRES KECAMATAN SANGATTA UTARA KOTA SANGATTA - RULLAH, ANSYA (KURVA S JURNAL MAHASISWA, 2014)
Subdistrict North Sangatta, especially on the road inpres is an area that is often flooded it is known by flood inundation maps and tables of points floodwaters City North Sangatta obtained from the Department of Public Works District. East Kutai. This thesis aims to analyze the ability of existing drainage channels (existing) to accommodate surface runoff and stream flow, condition, shape, construction and see the direction of the flow channel in the area of the floodwaters. Boundary problem in terms of this thesis is a hydrological analysis to analyze rainfall plans, rainfall intensity and time of concentration, while the analysis of hydraulics for analyzing the ability of the secondary channels that already exist (existing) in a location that is reviewed is the path Apt Pranoto District of North Sangatta to accommodate runoff and stream The method used is the method of data collection and analysis. The data used are primary data and secondary data are then analyzed based on the analysis of hydrology and hydraulics analysis and evaluated based on the value of the existing discharge chute with discharge plan value. To determine rainfall plans to use two types of distributions are widely used in the fields of hydrology, distribution Person Log III and Gumbel distribution, then take the value of rainfall over a period of 2, 5, 10, 25 years of Distribution Log Person III to be used in further calculations. The time is determined by the equation concentration tc = to + td, rainfall intensity with Mononobe method, discharge plan is calculated based on the Rational method and the evaluation of the channel cross section ≥ Qs equation QT.Rainfall value used to calculate the intensity of rainfall is the rainfall distribution value Logs Person III repeated periods of 2.5, 10, 25 years,. From the analysis of the dimensions of the channel turns all channels capable of accommodating the discharge channel to the next 25.